Influence of the resource potential of the region on the level of financial stability - Makhotaeva Marina; Nikolaev Mihail; Babkin Ivan (π-Economy)
The possibilities of effective use of regional resources are largely determined by the level of financial stability, which also plays an important role in overcoming depression and in ensuring the stable development of regional socio-economic systems. The purpose of the study is to examine the impact of the resource potential of the region on the level of financial stability and to substantiate the directions of its improvement in the context of typologized groups of regions. The analysis of scientific literature showed that when determining the financial stability of the region, a budget component is distinguished, which is characterized by solvency, budget balance and the level of financial independence of the regional budget, and an economic component, determined by the stable pace of economic development and the availability of investment resources to ensure expanded reproduction. The structuring of the resource potential made it possible to identify the following components: economic, investment, financial, innovative, production and labor potential. Clustering of 85 subjects of the Russian Federation by the size of resource potential and debt level using the k-means method made it possible to divide the regions into six groups. At the same time, for most of the regions, increasing financial stability is associated with increasing resource potential. The analysis showed that the solution to this problem is associated with the formation of a favorable investment climate and the development of production potential. The study of the dynamics of investments and industrial production made it possible to substantiate the directions for increasing the financial stability of regions in the context of the six identified clusters. For most of the subjects of the Russian Federation, the issue of ensuring financial stability is relevant. The exception is a small group of regions with high potential and low debt level. At the same time, these regions are also interested in improving financial stability, which, in particular, makes it possible to allocate additional resources to solve urgent socio-economic problems, as well as to conduct countercyclical budget policy. Increasing the financial stability of regions with low potential should be carried out on the basis of creating conditions for socio-economic development through the optimal use of the unique resources of the territories.